A decision support system applied to the teaching of mathematical programming models. (25th May 2010) - Rogerio Pinheiro, Placido; Brasil Filho, Amaury
An approach is proposed that will easily enable operational researchers and systems managers to obtain an optimised response of the generated model. The web-based decision support system (DSS) provides an environment for modelling and solving a model in mathematical programming. The environment uses a distributed architecture that turned the system extensible and very independent of platforms and the fabricants of solvers, also being able itself to connect proper optimisation software. The study demonstrates the importance that the internet has potential to be an important component in optimisation systems.